Effects of Microbial Starter Composition on Nutritional Contents and Pasting Properties of Fermented Cassava Flour - M.T.A.P. Kresnowati; L. Turyanto; A. Zaenuddin; K. Trihatmoko (Department of Chemical Engineering, Universitas Gadjah Mada, 2019)
Fermentation of cassava chips prior to drying and milling processes improves cassava flour quality: i.e. lower cyanogenic content, remove specific odour and colour. Composition of microbial starter applied to the fermentation may affect the microbial population during the fermentation and thus directs the process and the produced flour properties. This study mapped the effects of microbial starter composition on the microbial profiles during the fermentation and the corresponding nutritional contents as well as pasting properties of the produced fermented cassava flour (fercaf). Combinations of Lactobacillus plantarum, Bacillus subtilis and Aspergillus oryzae, that were selected based on their enzymatic activities, were evaluated. The addition of microbial starter was shown to affect the dynamics in microbial population during the fermentation. The addition of lactic acid bacteria accelerated the release of cyanogenic glycoside and starch conversion to simpler sugars, the addition of B. subtilis improved the disruption of cassava fibres, whereas the addition of A.oryzae was shown to increase the protein content of fercaf. The different microbial starter added to fermentation system also resulted in different pasting properties of fercaf. Microbial starter composition can be designed as such for the production of a particular flour property.